CORPORATE GOVERNANCE AND THEIR IMPLICATIONS FOR TRADING VOLUME IRAQ STOCK EXCHANGE CASE STUDYFOR THE DURATION OF 2010-2016 - HUSSEIN , HUSSEIN AHMED; MUSTAFA, KHANAF ISMAIL (Journal of Duhok University, 2020)
Financial markets are considered one of the most important components of the financial system in the economy. Contemporary literature has show growing concerns about corporate governance as it (increases nominal value and improves strategic performance) of businesses, as well as its sustainability of human and intellectual capital. The collapse of global financial markets has called on Iraqi experts - academics and practitioners - to direct their efforts to examine various aspects of corporate governance to ensure the public interest of individuals, companies and the state economy as a whole. The work of the Iraqi market for securities is characterized by disclosure and publication of daily, quarterly and annual data and fundamental modernity and analysis according to their indicators as well as the use of financial ratios, as well as the issuance of a directory of joint stock companies annually to indicate the financial position of the joint stock companies. The volume index is a barometer of the Iraqi market for securities, as it shows whether the level of the market (high or low). The research aims to clarify the effects of corporate governance in the volume of trading of the Iraqi market for securities through four indicators, namely: (volume index, average sectors that make up the market, growth rates between the base year 2010 and 2016, irregularities and stop trading companies). It is clear from the research that the Iraqi market for securities stable in terms of freedom of entry and exit of investors to and from the market, but there is instability in the volume of trading index during the period of research (2016-2010). After analyzing the data obtained, a number of conclusions were reached: 1. The banking sector is the most heavily traded sector by volume in all years of study 2012-2016. 2. The presence of follow-up by the Iraqi market for securities in activating the governance of companies listed in it through the following: A. The Securities Commission issued instructions No. (2) for the year 2011 on suspending the trading of companies if they lost any of the conditions of listing or if the company violated the disclosure requirements. B. The issuance of instructions by the Securities Commission No. (3) For the year 2011 on the rules for delisting the listed companies. In the light of the results, the researchers recommended a set of recommendations, including: 1. The need to encourage companies participating in the Iraqi Stock Exchange to comply with the principles of governance; because they lead to achieve transparency, and thus increase attractiveness of investments (domestic and foreign). 2. The need to find more effective means of communication with shareholders by listed companies in the market